All Days 2007
DOI: 10.2118/106276-ms
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Geomechanical Analysis on the Success of Hydraulic Fracturing: Lesson Learned from an Australian Coalbed Methane Gas Field

Abstract: Hydraulic fracturing is a widely used technology in the petroleum industry to increase production rates from low-permeability reservoirs. It has also been successfully applied to coalbed methane gas development in many occasions. This paper presents an Australian field case of coalbed methane gas development where expensive fracture treatments did not yield the expected benefits. A comprehensive integrated geomechanical analysis was performed to understand the underlying causes for the failure. The geomechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Most laboratory studies that report relative permeability in coals measured by steady state or unsteady state core flooding methods derive a crossover point water saturation fraction (S w ) exceeding 0.5, which is usually interpreted as the coal being water wet or hydrophilic (Conway et al, 1995;Durucan et al, 2013;Ham and Kantzas, 2011;Purl et al, 1991;Rahman and Khaksar, 2007;Shen et al, 2011). However, a problem with this standard approach is that it reports an average relative permeability for the core which assumes that the core has a uniform composition, homogenous wetting state and that the effects of capillary pressures are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Most laboratory studies that report relative permeability in coals measured by steady state or unsteady state core flooding methods derive a crossover point water saturation fraction (S w ) exceeding 0.5, which is usually interpreted as the coal being water wet or hydrophilic (Conway et al, 1995;Durucan et al, 2013;Ham and Kantzas, 2011;Purl et al, 1991;Rahman and Khaksar, 2007;Shen et al, 2011). However, a problem with this standard approach is that it reports an average relative permeability for the core which assumes that the core has a uniform composition, homogenous wetting state and that the effects of capillary pressures are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally measured relative permeability using coal cores in the laboratory under steady or unsteady methods detail a cross-point water saturation fraction in the relative permeability curve exceeding 0.5, implying coal is water wet (Conway et al, 1995a;Durucan et al, 2013;Ham and Kantzas, 2011;Purl et al, 1991;Rahman and Khaksar, 2007;Shen et al, 2011 (Kaveh et al, 2012;Saghafi et al, 2014), gas desorption (Ham and Kantzas, 2008;Ham and Kantzas, 2011), mineral matter (Gosiewska et al, 2002b) and liquid characteristics including ion concentration (Albijanic et al, 2010;Mishra et al, 2002) and pH (Chaturvedi et al, 2009). Coal rank is also another important factor that contributes to coal wettability, as high rank coal, such as anthracite are not water-wet, yet low rank coal like peat has both a high moisture content and is waterwet (Moore, 2012).…”
Section: Research Problemmentioning
confidence: 99%
“…Some studies that measured relative permeability of coal cores in the laboratory using steady or unsteady method detailed a cross point water saturation fraction exceeding 0.5, implying coal is water wet (Conway et al, 1995a;Durucan et al, 2013;Ham and Kantzas, 2011;Purl et al, 1991;Rahman and Khaksar, 2007;Shen et al, 2011). However, experimental results have also shown that coal may have a mixed wetting state based on mineralisation, pressure, gas desorption, rank, lithotype, and pH (Gash et al, 1992;Ham and Kantzas, 2011).…”
Section: Relative Permeability Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of the stress tensor properties with pre-existing coal fractures determines which fractures are 'critically' stressed and hence more likely permeable , see review in Zoback 2007. Rahman and Khaksar (2007) raise the spectre of complex hydraulic fracture propagation and potential stimulation failures in complex in-situ stress environment, particularly in reverse stress regimes.…”
Section: Stress Characterisationmentioning
confidence: 99%